Java EE 7 with GlassFish 4 Application Server - Heffelfinger, David R. (Packt Publishing, 2014)
This book is a practical guide and follows a very user-friendly approach. The book aims to get the reader up to speed in Java EE 7 development. All major Java EE 7 APIs and the details of the GlassFish 4 server are covered followed by examples of their use.If you are a Java developers who wants to become proficient with Java EE 7 this book is ideal for you. Readers are expected to have some experience with Java and to have developed and deployed applications in the past, but don't need any previous knowledge of Java EE or J2EE. It teaches the reader how to use GlassFish 4 to develop and deploy applications